Metal‐Free Decarboxylative Cyclization/Ring Expansion: Construction of Five‐, Six‐, and Seven‐Membered Heterocycles from 2‐Alkynyl Benzaldehydes and Cyclic Amino Acids1. Issue 33 (6th July 2015) - Samala, Srinivas; Singh, Gajendra; Kumar, Ravi; Ampapathi, Ravi Sankar; Kundu, Bijoy
Abstract A one pot synthesis of 1H‐benzo[g]indoles, tetrahydrobenzo[h]quinolines, and naphtho[1, 2‐b]azepines from 2‐alkynyl benzaldehydes and cyclic amino acids is reported. The salient feature of the strategy involves formation of three new bonds (one CN and two CC bonds) by a metal‐free decarboxylation/cyclization/one‐carbon ring expansion sequence in one pot.